SCREENING OF THALASSAEMIA IN THE EXTENDED FAMILY MEMBERS OF THALASSAEMIA CHILDREN (Journal of Medical & Health Sciences Review, 2025)
A dangerous blood condition that can run in families is thalassemia. It poses a significant health risk, particularly in regions where the gene is prevalent. Examinations were performed on 320 members of the families of children who were diagnosed with thalassemia in order to establish who was a carrier and who was not. According to the findings, roughly 26% of people were carriers, which is a noteworthy percentage. This emphasizes how crucial it is to screen family members and offer genetic counseling in order to help stop the condition from being inherited by subsequent generations. We can lower the number of new cases and assist families in making educated decisions by spreading knowledge about thalassemia and providing support.